Heritable Cancer Syndromes Related to the Hypoxia Pathway - Henegan, John Clark; Gomez, Christian R. (Frontiers in Oncology, 2016)
Families of tumor-suppressor genes, such as those involved in homologous recombination or mismatch repair, contain individual genes implicated in hereditary cancer syndromes. Collectively, such groupings establish that inactivating germline changes in genes within pathways related to genomic repair can promote carcinogenesis. The hypoxia pathway, whose activation is associated with aggressive and resistant sporadic tumors, is another pathway in which tumor-suppressor genes have been identified. Von Hippel-Lindau disease, some of the hereditary paraganglioma-pheochromocytoma syndromes, and the syndrome of hereditary leiomyomatosis and renal cell carcinoma are heritable conditions associated with genes involved or associated with the hypoxia pathway. This review links these heritable cancer syndromes to the hypoxia pathway while also comparing the relative aggression and treatment resistance of syndrome-associated tumors to similar, sporadic tumors. The reader will become aware of shared phenotypes (e.g. pheochromocytoma-paraganglioma, renal cell carcinoma) among these three hypoxia-pathway asscociated heritable cancer syndromes as well as the known associations of tumor aggressiveness and treatment resistance within these pathways.